Integración de un sistema de gestión para gases de efecto invernadero con los lineamientos generales de calidad, seguridad y ambiente en la operación de equipos de tierra en una aerolínea - Muñoz Vasco, Rubén Santiago (2015)
The present research is aimed at defining the guidelines to integrate a Management System for Greenhouse Gases criteria of Quality ISO 9001, Environment ISO 14001 and Occupational Health and Safety OHSAS 18001 for ground operations in an airline, with the objective of harmonizing compliance requirements and achieve resource optimization. Although the regulatory requirements listed are from different sources and each have different approaches, they have common elements, making it possible to integrate them within a systems approach to management of ground operations for airlines, ensuring compliance with standards through the synergies of different management systems, in favor of optimization of resources required for the service. The research aims to create a methodology to provide guidance for ground operations for airlines wishing to design, document, implement and maintain an Integrated Management System of Greenhouse Gases criteria of Quality, Safety and Environment System. To achieve this objective, the investigation presents a functional plan for the design and implementation as well as the Integrated Management System Manual that sets the organizational philosophy and structure, as well as the relationships between the procedures and requirements of the standards integrated occurs, which creates the best tool for the implementation of Management System.